Feasibility Study of Using Ground Granulated Blast Furnace Slag as Modified Cement Composites in 3D Printing Mortar - Sayed Mustaffa Kamal, Sharifah Intan Amira; Norhafizah Salleh, (Recent Trends in Civil Engineering and Built Environment, 2024)
There's the layer bonding, which is a weakness in the manufactured printing part. It's worth mentioning that as the time between layers increases, the bonding strength diminishes and the wastes that had been produced by Malaysian had been estimated that to continue to increase as the population grows and more worryingly it will demand saturation on landfills across the country. By having GGBS as waste material can help contribute to waste reduction and strength layer bonding. The objective of this study is to define the chemical composition of Ground Granulated Blast Furnace Slag (GGBS) and to determine the compressive strength of mortar containing GGBS as partial cement replacement. There are four samples using different proportions of materials which is the mixture with 0%, 30%, 40% and 50% of GGBS by fixing 0.5w/c ratio and w/binder ratio. Those tests had been performed to achieve the objective which are compressive test, flow test and collapse test. Those testing has been complied with ASTM standard procedures to conduct the study. From the observation, there are increments for the strength in 7days but decrease when at 50% on 28days. The workability for 0.5w/binder ratio toward this study increased within percentage GGBS replacement increase. The buildability for them has incremented and decreased at 50% GGBS replacement. Those studies found that using rectangular shape nozzle with bigger opening which is 20mm can gained best result of buildability during collapse test also past research mentioned the same outcome. The percentage of GGBS replacement is the must increase in the future replacement with a 0.5w/c ratio and w/binder ratio.  For future work suggest testing with different w/c ratios which below than 0.5 due to higher workability can contribute to lower strength.